Permasalahan Pengerjaan Pondasi dan Dinding pada Proyek Perumahan - Nurdiani, Nina (Bina Nusantara University, 2012)
Good housing quality will make the age of building more longer, and occupants will be more comfortable to live in the house. Due to high of growth of housing projects and the need to finish quickly, developers often pay less attention to the quality of the building work. Many problems occurred in the work area during the construction of housing projects. It could hinder the work and affect the physical quality of buildings after the construction period. This study explores the issue of housing project development, focusing on foundation and wall consruction, as well as the solution. The study is conducted by field observations and literature review related foundation and wall consruction. The locations are taken from five housing projects in Jakarta built by private developers in 2008-2010. The results provide information that the issue on foundation and wall consruction is very important because it is associated with the strength and robustness of the building, as well as the convenience of staying after the construction finished. If the problems can be addressed and resolved early, the risk of decline in the quality of the building can be controlled, avoided or eliminated. Otherwise, it can lead to a decrease in housing quality prematurely.